Thoracoscopic Ablation of Critically Located Liver Tumors: A Safety and Efficacy Cohort Study - Cillo, Umberto; Finotti, Michele; Di Renzo, Chiara; Vitale, Alessandro; Zanus, Giacomo; Gringeri, Enrico; Bertacco, Alessandra; Polacco, Marina; D'Amico, Francesco (Frontiers in Surgery, 2021)
Background: Liver resection represents the first curative indication to treat primary and secondary hepatic tumors. Thoracoscopic liver ablation is a viable mini invasive alternative treatment, especially for patients with previous multiple abdominal surgeries. The aim of the study was to evaluate the efficacy, safety and recurrence rate of thoracoscopic ablation for liver tumors. Methods: Retrospective analysis of a prospective database of patients with liver tumors, treated with thoracoscopic trans diaframmatic ablation (MWA or RFA) at our institution from 2012 to 2018. Efficacy of ablation was evaluated according to mRECIST criteria, based on CT/RMN images. Patient demographics, operational characteristics, and complications were recorded. Results: A total of 13 nodules were treated in 10 patients, median age of 65.5 years. Perioperative mortality was 0%. Overall morbidity was 40%, with Dindo‐Clavien complications ≥3 in 10%. The overall 1‐, 2- and 3‐years survival rates were 80%, 58% and 58%. Complete response was obtained in 83.3% of nodules at 3 months. At follow up (20.95 months), the local tumor progression rate was 30%, with an intra-segmental-recurrence of 30%, and an intra-hepatic-recurrence of 30%. Conclusion: Thoracoscopic trans diaframmatic ablation proved to be safe and effective to treat liver tumors when abdominal approach is not feasible. Considering the low morbidity it is a viable option to treat patients with recurrent disease and/or previous multiple abdominal surgeries.